Deposition of NiO thin films by sol-gel spin coating: effect of annealing temperature on structural, optical and electrical properties / Norfarariyanti Parimon … [et al.] - Parimon, Norfarariyanti; Mamat, Mohamad Hafiz; Zoolfakar, Ahmad Sabirin; Malek, Mohd Firdaus; Banu, I. B. Shameem (Universiti Teknologi MARA Press (Penerbit UiTM), 2020)
Nickel oxide (NiO) thin films were deposited by sol-gel spin coating approach and annealed at different temperatures of 300 °Ϲ, 400 °Ϲ, and 500 °Ϲ. Herein, the influence of the heattreated process on NiO thin films to the morphological, structural, optical, and electrical properties were investigated. The field emission scanning electron microscopy reveals that the grain morphology is clearly visible with a random orientation at the highest temperature of 500 °Ϲ. Subsequently, the grains are gradually blurred and not clearly seen with the decreases of the annealing temperature. The X-ray diffraction pattern shows that a strong intensity peak of NiO is observed for the sample at an annealing temperature of 500 °Ϲ indicating the enhancement of the film crystallinity is at the highest temperature. The average crystallite sizes of NiO thin films were calculated using the Scherrer formula and yielded various sizes with a maximum value of 19 nm for 500 °Ϲ-annealed sample. The bandgap energies of the samples were estimated from the Tauc’s plot to be in the values between 4.08 to 4.11 eV. The electrical properties indicate that the resistance and the resistivity of NiO thin films decrease as the annealing temperature increased. From the results, it shows the potential of these NiO thin films for the application of sensing measurement.